Psychometric Analysis of a School Social Climate Scale: Input Elements for the Investigation and Promotion of Well-Being - Bravo-Sanzana, Mónica; Miranda-Zapata, Edgardo; Miranda, Horacio (Frontiers in Psychology, 2020)
School social climate (SSC) from a multidimensional perspective is a focus of great interest in international research and educational and well-being public policies due to the high prevalence of interpersonal violence in adolescents, currently considered a global public health problem. The object of the present study was to assess the psychometric measurement capacity of a set of items to evaluate SSC in the Student Context Questionnaire of the Chilean Education Quality Measurement System (SIMCE). The sample analyzed consisted of second year high school students who replied to a Student Context Questionnaire in 2015 (n~158,572). Exploratory and confirmatory factorial analyses were carried out in a measurement model in order to identify the presence of constructs and items of high homogeneity. The results showed an acceptable to good fit in the final model, which consisted of fifteen latent constructs, and also showed invariance for school administrative dependencies and invariance for sex. All the above implies a contribution to the public organisms that create standardized tests along with the investigation in CSE measurement in order to prevent future violent behaviors, contribute to reducing interpersonal violence and improve the well-being of the educational community.